Peran Guru sebagai Pendidik dalam Membentuk Karakter Peserta Didik di SDN 131 Tanjung - Kholidah Nur; Anwar Nasution; Diana; Mhd. Ilham; Nur Saadah Lubis; Nurmia Hasibuan; Rostina Rangkuti (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to describe the role of teachers in shaping the character of students at SDN 131 Tanjung and to analyze how Islamic educational values are reflected in the learning process. Based on the results of interviews, teachers explained that their role is not limited to delivering material, but also includes guiding students' morals, character, and personality. Character building is carried out through role modeling, daily habits, and effective communication between teachers, parents, and the school environment. Teachers instill the values of honesty, discipline, responsibility, cooperation, and mutual respect through simple routines such as greetings, prayers, classroom discipline, and polite behavior. Role modeling is the most effective method because students tend to imitate what they see from their teachers. Obstacles encountered include differences in student character and a lack of support from some parents. This study also reviews the concept of education from an Islamic perspective, including the roles of mu'allim, murabbiy, mudarris, mu'addib, and mursyid as moral guides. Overall, the results of the study confirm that the role of teachers is crucial to the success of character building and the quality of learning, so teachers are required to be professional, moral, and inspiring educators.